텐서플로우를 이용한 주가 예측에서 가격-기반 입력 피쳐의 예측 성능 평가 - 송유정(Yoojeong Song); 이재원(Jae Won Lee); 이종우(Jongwoo Lee) (정보과학회 컴퓨팅의 실제 논문지, 2017)
The stock price prediction for stock markets remains an unsolved problem. Although there have been various overtures and studies to predict the price of stocks scientifically, it is impossible to predict the future precisely. However, stock price predictions have been a subject of interest in a variety of related fields such as economics, mathematics, physics, and computer science. In this paper, we will study fluctuation patterns of stock prices and predict future trends using the Deep learning. Therefore, this study presents the three deep learning models using Tensorflow, an open source framework in which each learning model accepts different input features. We expand the previous study that used simple price data. We measured the performance of three predictive models increasing the number of priced-based input features. Through this experiment, we measured the performance change of the predictive model depending on the price-based input features. Finally, we compared and analyzed the experiment result to evaluate the impact of the price-based input features in stock price prediction. 과거부터 현재까지 주식시장에 대한 주가 변동 예측은 풀리지 않는 난제이다. 주가를 과학적으로 예측하기 위해 다양한 시도 및 연구들이 있어왔지만, 아직까지 정확한 미래를 예측하는 것은 불가능하다. 하지만, 주가 예측은 경제, 수학, 물리 그리고 전산학 등 여러 관련 분야에서 오랜 관심의 대상이 되어왔다. 본 논문에서는 최근 각광 받고 있는 딥러닝(Deep-Learning)을 이용하여 주가의 변동패턴을 학습하고 미래를 예측하고자한다. 본 연구에서는 오픈소스 딥러닝 프레임워크인 텐서플로우를 이용하여 총 3가지 학습 모델을 제시하였으며, 각 학습모델은 각기 다른 입력 피쳐들을 받아들여 학습을 진행한다. 입력 피쳐는 이전 연구에서 사용한 단순 가격 데이터를 확장해 입력 피쳐 개수를 증가시켜가며 실험을 하였다. 세 가지 예측 모델의 학습 성능을 측정했으며, 이를 통해 가격-기반 입력 피쳐에 따라 달라지는 예측 모델의 성능 변화 비교 분석하여 가격-기반 입력 피쳐가 주가예측에 미치는 영향을 평가하였다.